Review of the Evagetes crassicornis species-group (Hymenoptera: Pompilidae), with description of new species - Lelej, Arkady S.; Loktionov, Valery M. (Zootaxa, 2009)
The three species and two subspecies of the Evagetes crassicornis species-group are reviewed. A new species, Evagetes orientalis, sp. nov., is described and illustrated from the Russian Far East. A lectotype of Pompilus sahlbergi F. Morawitz 1893 is redescribed. Evagetes crassicornis crassicornis (Shuckard) is recorded for the first time from Ukraine, Georgia, Kazakhstan, and Alaska. A key is presented for both sexes of this species-group.